The Cost-Effectiveness of Three Screening Alternatives for People with Diabetes with No or Early Diabetic Retinopathy - Rein, David B (Blackwell Science Inc, 2011)
OBJECTIVE: To determine whether biennial eye evaluation or telemedicine screening are cost-effective alternatives to current recommendations for the estimated 10 million people aged 30–84 with diabetes but no or minimal diabetic retinopathy. DATA SOURCES: United Kingdom Prospective Diabetes Study, National Health and Nutrition Examination Survey, American Academy of Ophthalmology Preferred Practice Patterns, Medicare Payment Schedule. STUDY DESIGN: Cost-effectiveness Monte Carlo simulation. DATA COLLECTION/EXTRACTION METHODS: Literature review, analysis of existing surveys. PRINCIPAL FINDINGS: Biennial eye evaluation was the most cost-effective treatment option when the ability to detect other eye conditions was included in the model. Telemedicine was most cost-effective when other eye conditions were not considered or when telemedicine was assumed to detect refractive error. The current annual eye evaluation recommendation was costly compared with either treatment alternative. Self-referral was most cost-effective up to a willingness to pay (WTP) of U.S.$37,600, with either biennial or annual evaluation most cost-effective at higher WTP levels. CONCLUSIONS: Annual eye evaluations are costly and add little benefit compared with either plausible alternative. More research on the ability of telemedicine to detect other eye conditions is needed to determine whether it is more cost-effective than biennial eye evaluation.